Reflective Practice and Teaching Philosophy: Insights from Experienced EFL Teachers in Indonesia - Maharani, Suci; Putra, Rahmat Agung Azmi (English Department, Universitas Negeri Surabaya, 2025)
Understanding teachers’ teaching philosophy is central to their professional growth, yet research on experienced EFL teachers’ reflective practice in Indonesia remains limited. This study addresses the gap by exploring how experienced teachers conceptualize their teaching philosophy through reflection. A qualitative case study was conducted with three experienced Indonesian EFL teachers, each holding more than nine years of teaching experience and a master’s degree in English education. Data were collected through six rounds of semi-structured interviews and reflective journals, guided by established reflective frameworks. Triangulation was applied to ensure trustworthiness, and thematic analysis was used to interpret the data. Eight themes emerged: (1) the role of English in formal schooling, (2) external influences on teaching, (3) perceptions of being a teacher, (4) experiences of teaching English, (5) challenges in English instruction, (6) strategies for managing classroom problems, (7) adaptation of teaching methods, and (8) critical incidents shaping professional identity. These findings highlight how personal experiences, contextual constraints, and reflective engagement shape teachers’ philosophies and practices. The study demonstrates that reflective practice enables teachers to align pedagogical choices with their evolving philosophy, fostering professional identity and responsiveness to learners’ needs. The results resonate with global literature on reflective teaching while emphasizing the Indonesian context.